Ties Coordinating Committee Mtg. @ TI [Impact of Proposed Cigarette Tax Increase in Various States] (Tufts Archival Research Center, 2007)
Series of reports conducted by the American Economics Group on the impact of proposed cigarette taxes in various states. Includes analysis of Maryland, Minnesota, Montana, and New Mexico. Focuses on the interstate competition and competition provided by tax free Indian reservations. Analyzes financial/commercial losses and convenience store losses.